Pengaruh Religiusitas Terhadap Kinerja Karyawan (Studi Kasus Pada Suryamart Soekarno-Hatta Ponorogo Tahun 2019) - Imam Haryadi; Luthfi Noor Mahmudi (University of Darussalam Gontor, 2020)
Human resource is a crucial component in every company. Employee performance that is not optimal is a matter of achieving success. The purpose of this study is to determine the effect of the value of religiosity on employee performance (a case study on Suryamart Soekarno-Hatta Ponorogo 2019). This research uses quantitative descriptive methods. Data collection techniques using primary and secondary data, where primary data is done by conducting surveys, secondary data is obtained through a questionnaire or questionnaire. The data analysis technique used in this article is a simple linear regression analysis. The results of this study indicate that the variable Religiosity (X) has a t-count greater than t table, t-count equal to (8.761 > t table 2.026) and the significance value (Sig.) 0.00 < 0.05. So it can be concluded that the Religiosity variable (X) has a significant effect on Employee Performance (Y) and is known from the coefficient of determination (R Square) of 0.669 or can be stated with 66.9%, this figure implies that Religiosity as the dependent variable (X) affect Employee Performance by 66.9%. While the remaining 33.1% is influenced by other variables not examined in this study. This study indicates that the greater the value of Religiosity, the greater the effect on Employee Performance. For Suryamart Supermarkets, it is suggested to maintain and improve the value of Religiosity for employees so that all activities in the institution which could give a positive impact on business performance.